Hemispheric asymmetry in cross-race face recognition. - Correll, Joshua; Lemoine, Caroline; Ma, Debbie S. (Journal of Experimental Social Psychology, 2011)
This study examines two phenomena related to face perception, both of which depend on experience and holistic processing: perceivers process faces more efficiently in the right hemisphere of the brain (a hemispheric asymmetry), and they typically show greater recognition accuracy for members of their racial ingroup (a cross-race recognition deficit). The current study tests the possibility that these two effects are related. If asymmetry depends on experience, it should be particularly evident with (more familiar) ingroup faces; if cross-race recognition relies on holistic processing, it should be particularly evident for faces presented to the right hemisphere. Black and White participants viewed Black and White faces presented to either the left or right visual field. As predicted, participants showed a more pronounced asymmetry for ingroup (rather than outgroup) faces, and cross-race recognition deficits were more pronounced for stimuli presented to the left (rather than the right) visual field.